Circular Economy Applied to Sludge Minimization: The STAR Project - Maria Cristina Collivignarelli; Stefano Bellazzi; Alessandro Abbà (Membranes)
The management of biological sludge from wastewater treatment plants (WWTPs) poses a significant environmental challenge due to increasing sludge production and the presence of emerging pollutants. This study investigates an innovative solution by integrating a thermophilic aerobic membrane reactor (TAMR) into the sludge treatment line of a medium-size WWTP, aiming to minimize biological sludge output while enhancing resource recovery. The study involved a six-month monitoring of an industrial-scale TAMR system, assessing the reduction in volatile solids (VSs) in thickened sludge and evaluating the compatibility of TAMR residues with conventional activated sludge (CAS) systems. The TAMR unit, which achieved up to a 90% reduction in VSs, was combined with traditional CAS processes, forming the STAR (Sludge Treatment and Advanced Recycling) configuration. This configuration reduced sludge output to just 10% of conventional levels while enabling the recirculation of nutrient-rich liquid effluents. Both batch and continuous respirometric tests demonstrated the biological treatability of TAMR residues, highlighting their potential reuse as external carbon sources and their positive impact on CAS system performance. The findings suggest that integrating mesophilic and thermophilic systems can significantly improve sludge management efficiency, lowering both operating costs and environmental impacts.